Transcriptional Regulation of Arabidopsis Polycomb Repressive Complex 2 Coordinates Cell-Type Proliferation and Differentiation. Issue 10 (20th September 2016) - de Lucas, Miguel; Pu, Li; Turco, Gina; Gaudinier, Allison; Morao, Ana Karina; Harashima, Hirofumi; Kim, Dahae; Ron, Mily; Sugimoto, Keiko; Roudier, Francois; Brady, Siobhan M.
Abstract : Chromatin-modifying PRC2 subunits were shown to regulate root vascular development, and their upstream regulators were identified and shown to control the expression of PRC2 downstream targets. Abstract: Spatiotemporal regulation of transcription is fine-tuned at multiple levels, including chromatin compaction. Polycomb Repressive Complex 2 (PRC2) catalyzes the trimethylation of Histone 3 at lysine 27 (H3K27me3), which is the hallmark of a repressive chromatin state. Multiple PRC2 complexes have been reported in Arabidopsis thaliana to control the expression of genes involved in developmental transitions and maintenance of organ identity. Here, we show that PRC2 member genes display complex spatiotemporal gene expression patterns and function in root meristem and vascular cell proliferation and specification. Furthermore, PRC2 gene expression patterns correspond with vascular and nonvascular tissue-specific H3K27me3-marked genes. This tissue-specific repression via H3K27me3 regulates the balance between cell proliferation and differentiation. Using enhanced yeast one-hybrid analysis, upstream regulators of the PRC2 member genes are identified, and genetic analysis demonstrates that transcriptional regulation of some PRC2 genes plays an important role in determining PRC2 spatiotemporal activity within a developing organ.